Hydroelectrolytic and Acid–Base Parameters after 80 to 115 km Endurance Races (Raid Uruguayo) and Their Association with the Comfort Index - Gonzalo Marichal; Pablo Trigo; Carlos Soto; Ana Meikle; Gonzalo Suárez (Animals, 2023)
The Raid Uruguayo (RAID) is an equestrian endurance competition. This study characterized the hydroelectrolytic parameters (Na+, K+, Cl−, tCa++, and iCa++), hematocrit (Ht), total plasma protein (TPP), and blood pH from 900 equine athletes (finishers and non-finishers) competing over distances of 80 to 115 km under different climate conditions. Paired blood samples were taken prior to the start of the competition (sample 1) and at the end of the race or at the time of leaving the competition (sample 2). The association of the comfort index (CI: low, moderate, and high) with blood parameters was evaluated. Of the 900 horses included, 550 were not able to finish the trial. The comfort index was not associated with success in completing the race. In the horses that finished the race, the CI was not associated with Ht, pH, TPP, or Na+ concentrations in samples taken after finishing the RAID. In contrast, the decreases in chloride, K+, tCa++, and iCa++ concentrations found after the race were more pronounced at moderate and high CI values when compared with low CI values. In horses that did not finish the race, the CI was associated with all variables except for Ht. The data confirmed the relevance of considering the impact of the comfort index in hydroelectrolytic losses in the RAID, as it influence ssuccess or failure in the performance of endurance horses finishing the competition.